PENGARUH WORK-FAMILY CONFLICT TERHADAP ABSENTEEISM DAN TURNOVER INTENTION (STUDI PADA KARYAWATI PERUSAHAAN PERBANKAN DI MALANG) (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2012)
Work-family conflict is a form of inter-role conflict in which the role pressures from the work and family field contradictory. This means that participation in the family role or job complicate implementation responsibilities in other roles. Conflict between work and family is important for organizations and individuals as it can lead to a number of negative effects, such as increased absenteeism, increased turnover, decreased performance and physical health and poor mental. This study aims to determine the effect of work family conflict and family work conflict on absenteeism and turnover intention.A study conducted on employee banking company in Malang, with 94 employees as respondents.The results of multiple regression showed that the higher family - work conflict, the absenteeism from work will also be high, and the higher the family - work conflict, the turnover intention will also be high. When someone runs a variety of roles as workers, as a partner in the household and as a parent, every role will require time, energy and commitment. The difficulty to be able to balance the demands of family and job demands encourage employees to move work and look for another job which they think can set the time, both for the family and the job.